Improvements in the quality of working life in three Japanese industries / by S. Takezawa...[et al] - "Takezawa, S." (Geneva, 1985)
This monograph is a product of the two ILO research contrasts entitled "Improvements in the Quality of Working Life in Selected Japanese Industries", both entered in 1976. One contract went to the Japan Institute of Labour for the technical assistance, while the other came to the author as co-ordinator of the project. The presnt author assumes the total responsibility for writing this report.
Keywords: Industrial management -Japan.